Peran Shared Leadership Dalam Keberhasilan Proyek: Mediasi Knowledge Sharing Dan Perceived Cohesion Serta Moderasi Trust - Muhammad Riansyah Prasetya Ibrahim; Humairah Izmi Azifah; Muh Fauzan; Leila Lathifah Salsabila; Carolina Novi Mustikarini; Arya Panaungi Amril (STIM-LPI Makassar, 2026)
This study examines the effect of shared leadership on project success, highlighting the mediating roles of knowledge sharing and team cohesion, as well as the moderating role of trust within the team. Data were collected from 53 respondents through an online survey to analyze their experiences in dynamic project environments, particularly in the information technology sector. The analytical method employed was Structural Equation Modeling–Partial Least Squares (SEM-PLS) to process the data and test the relationships among variables. The findings indicate that shared leadership has a positive effect on project success, as it enhances team involvement and encourages more collaborative decision-making. However, knowledge sharing and team cohesion do not function as significant mediators in this relationship. Based on these results, the study suggests that although shared leadership can strengthen team dynamics, other factors such as communication effectiveness and project implementation strategies exert a greater influence on project success. Therefore, project leaders should focus on developing shared leadership models while ensuring effective communication and team coordination mechanisms to optimize project outcomes.